Respon Pertumbuhan Bibit Tanaman Cabai Rawit (Capsicum frutescens) dengan Aplikasi Vitamin B1 - Christy, Julieta; Sinaga, Robert; Gultom, Daniel Maruli Tua (Universitas Quality, 2023)
Cayenne pepper is a commodity that is quite high in demand in Indonesia. The problem in chili nurseries is to ensure that the plants grow vigor after the transplanting process is carried out. For this reason, it is necessary to provide vitamins to accelerate the adaptation process so that chili plants can grow optimally. To overcome this problem, in this study the application of vitamin B1 (thiamine) was carried out at the beginning of transplanting cayenne pepper seedlings from the nursery. The purpose of this study was to determine the effect of the application of vitamin B1 on cayenne pepper seeds and the best concentration of vitamin B1. This research will be carried out for three months, from early June to the end of August 2023. The research will be conducted in Kelurhan Sidomulyo, Kecamatan Medan Tuntungan, Kota Medan. The research design was a completely randomized design with 1 factor and 3 replications. The treatment factor was the concentration of vitamin B1 with 4 levels. V0: control; V1: 0.5 ml/l vitamin B1; V2: 1 ml/l vitamin B1; and V3: 1.5 ml/l vitamin B1. The results showed that the administration of vitamin B1 (thiamine) during transplanting had an effect on the growth of cayenne pepper seedlings.